Indian Rattan Distribution - an Update - Renuka, C. (Indian Forester, 1999)
An analysis of distribution of Rattans in the 3 different major areas in India shows that much change has taken place in its distribution over the years. Even though the reasons differ in each of the 3 major distribution areas, the ultimate result is over-exploitation and habitat destruction. As a result the broad genetic base is getting reduced alarmingly. Hence effective measures are to be taken to conserve and propagate Rattans.